2016
DOI: 10.1159/000438620
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazole-Dithiocarbamate Hybrids, a Group of Novel Cell Active SIRT1 Inhibitors

Abstract: Background/Aims: Human SIRT1 is reported to be involved in tumorgenesis, mainly due to its modulating effect on p53 by deacetylation on lysine382. A large quantity of SIRT1 inhibitors was applied in chemotherapeutic study, but few of them were applied into clinical trials. Methods and Results: In the current study, a novel series of compounds with 1,4-bispiperazinecarbodithioic acid methyl esters scaffold were characterized to have inhibitory potency to SIRT1 by molecular docking and biochemical evaluation. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Dithiocarbamate derivatives have strong affinity toward transition metals; pyrrolidine dithiocarbamate (PDTC) is a representative compound, exhibiting diverse biological effects [ 20 22 ]. In view of instability and stronger affinity toward transition metals, especially zinc and copper ions, the thiol-modified dithiocarbamate derivatives were prepared to enhance their stability and improve their biological activity [ 23 , 24 ]. In the present study, a new synthesized dithiocarbamate derivative (DpdtbA) showed better antitumor activity against gastric cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Dithiocarbamate derivatives have strong affinity toward transition metals; pyrrolidine dithiocarbamate (PDTC) is a representative compound, exhibiting diverse biological effects [ 20 22 ]. In view of instability and stronger affinity toward transition metals, especially zinc and copper ions, the thiol-modified dithiocarbamate derivatives were prepared to enhance their stability and improve their biological activity [ 23 , 24 ]. In the present study, a new synthesized dithiocarbamate derivative (DpdtbA) showed better antitumor activity against gastric cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple docking studies and biochemical assays have shown that the indole molecules mainly bind at the catalytic site to inhibit the deacetylating activity of the sirtuins (Napper et al, 2007;Suenkel et al, 2013;Pulla et al, 2014;Panathur et al, 2015). Other than indole molecules, benzofuran (Xu et al, 2017), 2anilinobenzamide analogues (Suzuki et al, 2012), 1,4bispiperazinecarbodithioic acid methyl esters series (Zheng et al, 2016), chromanone derivative (Fridén-Saxin et al, 2012), oxycoumarin and diphenyl derivatives (Padmanabhan et al, 2016), pyrazolone and isoxazol-5-one cambinol analogues (Medda et al, 2009;Mahajan et al, 2014), 6,7dichloro-2-oxindole series (Huber et al, 2010;Verçoza et al, 2017) and a series of thieno [3,2-d] pyrimidine-6-carboxamides (Cui et al, 2014) were reported to have high inhibition for sirtuin activity. Most of these inhibitors have not been tested on NDD models.…”
Section: Name Of the Compound Structure Resolutionmentioning
confidence: 99%
“…Owing to the infeasibility for targeting lncRNA in the clinical work now, we wanted to target SIRT1 to achieve the effect of inhibiting this signal axis in tumors. Recently, many new drugs targeting SIRT1 have been designed [ [58] , [59] , [60] , [61] ]. But the effect and toxicity of these drugs needs more in vitro and vivo assays to test.…”
Section: Discussionmentioning
confidence: 99%